Public Opinion about Actions to Protect Water Resources - Tatiana Borisova; John Brett; Cassel Gardner (EDIS)
FE842, a 9-page illustrated report by Tatiana Borisova, John Brett, and Cassel Gardner, summarizes the results of a public survey about the protected water resources in Florida. Published by the UF Department of Food and Resource Economics, October 2010.